HUBUNGAN EXPRESSED EMOTION KELUARGA DAN PEER SUPPORT DENGAN SUICIDE IDEATIONPADA REMAJA DI SMP N 8 MANADO - Gaol, Apryani Lumban; Buanasari, Andi; Bidjuni, Hendro (Universitas Sam Ratulangi, 2021)
Abstract Background Family expressed emotionand peer support is important in shaping the emotional and mentality af a teenager. The purpose of this study is to find out prove the relationship between family expressed emotion and peer support with suicide ideation in Junior High School 8 Manado. The research method used to prove the hypothesis of this study is a quantitative approach, cross sectional, with the Spearman Rank correlation technique. The sample was taken using non-probability techniques, purposively. The sample size was 83 respondents in Junior High School 8 Manado. The results of the study prove that both hypotheses can be accepted. H1 test shows the level of strength (closeness) between variabels is moderate (0,369), positive direction, and significant (p = 0, 001 < Î± = 0,05). H2 test shows the level of strength (closeness) between variabels is moderate (-0,218), negative direction, and significant (p = 0, 048< Î± = 0,05). Conclution : there is a moderate, positive and negative and significant relationship between family expressed emotion (36,9%),peer support (-21,8%)with suicide ideation. Suggestions, for school to improve mental health education services and counseling to address adolencent mental health problem and efforts to tackle of suicide ideation in adolescents.Keywords: Family Expressed Emotion; Peer Support; Suicide IdeationAbstrak Ekspresi emosi keluarga dan dukungan teman sebaya merupakan hal yang penting dalam pembentukan emosional dan mentalitas remaja.Tujuan dari penelitian ini yaitu untuk mengetahui dan membuktikan hubungan antara ekspresi emosi keluarga dan dukungan teman sebaya dengan gagasan bunuh diri pada remaja di Smp N 8 Manado. Metode penelitian yang digunakan untuk membuktikan hipotesis penelitian ini adalah pendekatan kuantitatif, cross sectional, dengan teknik korelasi Rank Spearman. Sampel diambil dengan menggunakan teknik non-probabilitas. Jumlah sampel adalah 83 responden yang berada di SMP N 8 Manado. Hasil penelitian membuktikan kedua hipotesis dapat diterima. Uji H1 menunjukkan tingkat kekuatan (kedekatan) antara variabel cukup (0,369), arah positif, dan signifikan (p = 0, 001 < Î± = 0,05). Uji H2 menunjukkan tingkat kekuatan (kedekatan) antara variabel cukup (-0.218), arah negatif, dan signifikan (p = 0,048 <Î± = 0,05). Kesimpulan: ada hubungan yang moderat, positif dan negatif, serta signifikan antara ekspresi emosi keluarga (36,9%), dan dukungan teman sebaya (- 21,8%) dengan gagasan bunuh diri. Saran, bagi sekolah agar meningkatkan layanan pendidikan kesehatan mental dan bimbingan konseling untuk mengatasi masalah kesehatan mental remaja dan upaya untuk mengatasi gagasan bunuh diri.Kata Kunci : Ekspresi Emosi Keluarga; Dukungan Teman Sebaya; Gagasan Bunuh Diri.